QOL-09. EMOTION RECOGNITION IN PEDIATRIC BRAIN TUMOR PATIENTS: VIEWING PATTERNS AND WHITE MATTER STRUCTURE. Issue 2 (22nd June 2018) - Moxon-Emre, Iska; Bouffet, Eric; Laughlin, Suzanne; Skocic, Jovanka; de Medeiros, Cynthia; Mabbott, Donald J
Abstract: OBJECTIVE: Pediatric brain tumor patients display emotion recognition deficits, and eye-movement monitoring might help explain why. Identifying facial emotions is thought to rely on white matter (WM) that connects posterior, limbic and frontal brain regions. Thus, we examined if emotion recognition deficits are related to viewing patterns and to WM. METHODS: 22 patients treated for posterior fossa (PF) brain tumors and 12 healthy children participated in this study at SickKids (Toronto, Ontario). Participants completed the Diagnostic Analysis of Nonverbal Accuracy (DANVA-2), a computerized task that measures facial emotion recognition using photographs, while their eye-movements were recorded. Diffusion tensor imaging (DTI) was used to assess fractional anisotropy (FA). Whole brain voxel-based analyses were conducted to compare WM between patients and controls. Regional WM was correlated with the number of incorrect responses across all participants. RESULTS: Patients made more emotion recognition errors than controls (p=0.02). However, patients and controls did not differ in the number of fixations made on the photograph: (p=0.21), or in the total time spent looking at the photograph: (p=0.23). Relative to controls, patients had lower FA in many voxels across the brain (all p<0.05). Across all participants, FA was negatively correlated with the number of incorrect responses in the left temporal region (r=-0.503, p=0.005). CONCLUSIONS: Patients treated for brain tumors display emotion recognition deficits and WM damage. The emotion recognition deficits do not appear to result from inattention to the photographs. Our results suggest that left temporal WM may be important for successful emotion recognition.